2022
DOI: 10.1002/anie.202212151
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interfacial Bonding in Reduced Graphene Oxide Fiber Cathodes Containing Polypyrrole@sulfur Nanospheres for Flexible Energy Storage

Abstract: Flexible lithium sulfur batteries with high energy density and good mechanical flexibility are highly desirable. Here, we report a synergistic interface bonding enhancement strategy to construct flexible fibershaped composite cathodes, in which polypyrrole@sulfur (PPy@S) nanospheres are homogeneously implanted into the built-in cavity of self-assembled reduced graphene oxide fibers (rGOFs) by a facile microfluidic assembly method. In this architecture, sulfur nanospheres and lithium polysulfides are synergisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…51 As depicted in Figure 3E, the N 1s high-resolution spectrum reveals the presence of three contributions, which are mainly attributed to pyridinic N (397.8 eV), pyrrolic N (400.2 eV), and graphitic N (402.8 eV), respectively. 50,52 According to the integrated areas of N 1s in Figure 3E, the contents of pyridinic N and pyrrolic N are measured to be 27.7 and 62.2 atom % (Table S2), much higher than that of graphitic N (10.1 atom %). It is suggested that the introduction of high contents of pyridinic N and pyrrolic N in the carbon matrix is beneficial for creating more electroactive sites and boosting sodium storage performance.…”
Section: Resultsmentioning
confidence: 98%
“…51 As depicted in Figure 3E, the N 1s high-resolution spectrum reveals the presence of three contributions, which are mainly attributed to pyridinic N (397.8 eV), pyrrolic N (400.2 eV), and graphitic N (402.8 eV), respectively. 50,52 According to the integrated areas of N 1s in Figure 3E, the contents of pyridinic N and pyrrolic N are measured to be 27.7 and 62.2 atom % (Table S2), much higher than that of graphitic N (10.1 atom %). It is suggested that the introduction of high contents of pyridinic N and pyrrolic N in the carbon matrix is beneficial for creating more electroactive sites and boosting sodium storage performance.…”
Section: Resultsmentioning
confidence: 98%
“…The uniform graphene layer with tens of diameters on surface of HNVO nanobelt is beneficial for the electron transfer in charge/discharge process (Figure 1e). [46] The homogeneous distributions of C (derives from the graphene), Na, V and O elemental mapping images in Figure 1f. Such favorable morphology would contribute to the rapid kinetic reaction of charge carries.…”
Section: Resultsmentioning
confidence: 99%
“…Lithium-sulfur (Li-S) batteries with high theoretical capacity (1675 mAh g −1 ), high energy density (2567 Wh kg −1 ), environmental friendliness, and abundant resource of sulfur are widely applied in electronic devices and aerospace fields, etc. [214][215][216] However, several scientific and technological issues of sulfur-based cathodes impede the commercial application of Li-S batteries, including: [217][218][219] 1) Poor electron/ion conductivity of active sulfur and the produced lithium sulfide, resulting in low electrochemical reaction kinetics. 2) The high-volume expansion (80%) during the conversion process of sulfur to lithium sulfide, leading to the destruction and pulverization of the structure.…”
Section: Lithium-sulfur Batteriesmentioning
confidence: 99%